2007
DOI: 10.1097/mat.0b013e318031121f
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro Method for Assessing Biomaterial-Associated Platelet Activation

Abstract: The development of a nonthrombogenic artificial surface for use with indwelling sensors or catheters remains an elusive goal despite decades of ongoing research. In vivo studies are both labor intensive and costly, and are therefore an inefficient way to rapidly screen possible surface materials. The following in vitro model used glass, polyvinyl chloride (PVC), and polypropylene test tubes incubated with 111In-labeled rabbit platelets and illustrated that, despite equivalent platelet count and function, plate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Especially extracellular matrix‐like biomimetic surface modifications are a promising approach for further regulation of platelet activation (Li et al 2009). In prior studies, a positive influence of unspecific biomaterial surface topography and chemistry on platelet activation could be shown (Park, et al 2001; Kikuchi, et al 2005; Chuang & Lin 2007; LaFayette, et al 2007; Klein, et al 2010). However, the use of clinical applicable specific biomimetical surface modifications still has not quit experimental levels and remains exciting.…”
mentioning
confidence: 98%
“…Especially extracellular matrix‐like biomimetic surface modifications are a promising approach for further regulation of platelet activation (Li et al 2009). In prior studies, a positive influence of unspecific biomaterial surface topography and chemistry on platelet activation could be shown (Park, et al 2001; Kikuchi, et al 2005; Chuang & Lin 2007; LaFayette, et al 2007; Klein, et al 2010). However, the use of clinical applicable specific biomimetical surface modifications still has not quit experimental levels and remains exciting.…”
mentioning
confidence: 98%
“…It has been shown that platelet activation with consecutive degranulation and release of cytokines can be modulated by biomaterial surface properties like texture, chemical composition and electrical charge (Chuang & Lin 2007;LaFayette et al 2007). In oral and maxillofacial surgery, especially implant surfaces have been the focus of various in vitro studies.…”
mentioning
confidence: 99%
“…Further, the behaviour of platelets in biocompatibility testing is extremely important because these cells determine the initial events of the blood-clotting cascade. For example, metabolically inhibited platelets do not adhere to glass test tubes, whereas their passive adhesion to polypropylene tubes remains unchanged [13]. All these factors may contribute to disturbances in coagulation behaviour of uremic blood and thus influence the …”
Section: Testing With Healthy Donorsmentioning
confidence: 99%